Breeding habitat of Blue Crane (Anthropoides Paradiseus) in Mpumalanga Province, South Africa - Mmonoa, Ernest Mmaphuti (My University, 2009)
The aim of this study was to determine the breeding habitat of Blue Crane (Anthropoides paradiseus) by investigating the home range, habitat selection and habitat suitability. Geographic Information System (GIS) was used as the main tool for analysis. Home range sizes of Blue Cranes were studied during the breeding season using direct observation method. A 50% and 95% Adaptive Kernel was used to estimate home range sizes. The home range sizes were 9.0 ha and 43.5 ha for 50% and 95% Adaptive Kernel, respectively. All the nests were located within 50% Adaptive Kernel, often referred to as core area. The nests were located in agricultural land (mainly pasture) and close to water sources. Habitat selection was studied at nest sites (n = 74) and random sites (n = 200) following site attribute design. The Blue Crane showed a preference to breed in agricultural lands, close proximity to water sources, higher elevation areas, within north eastern sandy highveld vegetation, and north facing slope. The Blue Crane also avoided anthropogenic factors such as built-up land, roads and railway line. ModelBuilder extension of ArcGIS software was used to construct a breeding habitat suitability model for Blue Cranes. Nine habitat variables (water source, slope, aspect, elevation, land use, vegetation, built-up land, roads and railway line) were used in the model. The model was constructed using reclassify and weighted overlay command. Highly suitable sites accounted for 601, 448 ha, while moderately suitable sites accounted for 823, 593 ha, and least suitable sites accounted for 3, 000, 153 ha. This study demonstrated the effective use of GIS technology in analysing the breeding ecology of Blue Crane. The GIS technology provided capabilities for capturing and analysing varied and large data. It was also evident that availability of accurate and complete species data remains vital to enable the full utilization of the GIS technology.
Thesis (M.Sc. (Zoology)) --University of Limpopo, 2009
Keywords: Birds breeding; Habitat; Birds -- Habitat; Important bird areas; Birds -- Breeding -- South Africa -- Mpumalanga; Cranes (Birds) -- Breeding